Biomechanical comparison of the undercut thread design versus conventional buttress thread for the lag screw of the dynamic hip screw system - Liu, Fei; Feng, Xiaoreng; Zheng, Jianxiong; Leung, Frankie; Chen, Bin (Frontiers in Bioengineering and Biotechnology, 2022)
Objective: To compare the fixation stability of the lag screw with a undercut thread design for the dynamic hip screw (DHS) system versus the lag screw with the conventional buttress thread. Methods: The lag screws with the undercut thread (a flat crest feature, a tip-facing undercut feature) and buttress thread were both manufactured. Fixation stability was investigated using cyclic compressive biomechanical testing on custom osteoporotic femoral head sawbone. The forces required for the same vertical displacement in the two types of lag screw were collected to evaluate the resistance to migration. Varus angle was measured on X-ray images to assess the ability in preventing varus collapse. Finite element analysis (FEA) was performed to analyze the stress and strain distribution at the bone-screw interface of the two types of lag screws. Results: The biomechanical test demonstrated that the force required to achieve the same vertical displacement of the lag screw with the undercut thread was significantly larger than the lag screw with conventional buttress thread (p < 0.05). The average varus angles generated by the undercut and buttress threads were 3.38 ± 0.51° and 5.76 ± 0.38°, respectively (p < 0.05). The FEA revealed that the region of high-stress concentration in the bone surrounding the undercut thread was smaller than that surrounding the buttress thread. Conclusion: The proposed DHS system lag screw with the undercut thread had higher migration resistance and superior fixation stability than the lag screw with the conventional buttress thread.